Quality of Corporate Social Responsibility (CSR) Services at Bank Syariah Indonesia (BSI) in 2021 in the Perspective of Islamic Social Reporting (ISR) Index and Maqashid Syariah Index (MSI) - Nanda Pratiwi, Danisa; Setiyowati, Arin; Huda, Fatkur (Perisai : Islamic Banking and Finance Journal, 2023)
The government issues regulations through Limited Liability Company Law No. 40 of 2007 articles 66 and 74, which states that companies are required to report on the implementation of social and environmental responsibility which is often referred to as Corporate Social Responsibility (CSR). In carrying out its social responsibility, Bank Syariah Indonesia (BSI) must ensure that its operational system meets the benchmarks in CSR. To measure it, it is necessary to have a measuring instrument, namely using the Islamic Social Reporting (ISR) Index and the Maqashid Syariah Index (MSI), to fulfill CSR services to the community. This study aims to analyze the quality of CSR services at BSI 2021 in the ISR Index and MSI Perspective. This research was conducted using a type of library research (Library Research) using a qualitative approach. The validity of the data using source triangulation and data analysis techniques using data reduction. The results of the study show that the quality of CSR services in the 2021 BSI report has carried out CSR in accordance with seven principles including: ethical principles of ethics, principles of caliph protection, principles of honesty and trustworthiness, principles of halalan tayyiban, principles of fairness, principles of authenticity and credibility, and principles of charity. As for the quality of CSR activities specifically based on ISR items on the classification of funding and investment in zakat points, community classification in sadaqah, waqf, qardh hasan points, school scholarships, young generation development, community quality improvement, concern for children, and support social activities. And environmental classification at the point of environmental conservation and empowerment. Meanwhile, the quality of CSR services at BSI is in accordance with the Maqashid Syariah Index and fulfills the principles of individual education, achievement of justice, and public welfare, which are the foundations of this maqashid syariah not implemented by other Islamic banks.